Genome-Wide Identification, Sequence Variation, and Expression of the Glycerol-3-Phosphate Acyltransferase (GPAT) Gene Family in Gossypium - Cui, Yupeng; Ma, Jianjiang; Liu, Guoyuan; Wang, Nuohan; Pei, Wenfeng; Wu, Man; Li, Xingli; Zhang, Jinfa; Yu, Jiwen (Frontiers in Genetics, 2019)
Cotton is an economically important crop grown for natural fiber and seed oil production. Cottonseed oil ranks third after soybean oil and colza oil in terms of edible oilseed tonnage worldwide. Glycerol-3-phosphate acyltransferase (GPAT) genes encode enzymes involved in triacylglycerol biosynthesis in plants. In the present study, 85 predicted GPAT genes were identified from the published genome data in Gossypium. Among them, 14, 16, 28, and 27 GPAT homologs were identified in G. raimondii, G. arboreum, G. hirsutum, and G. barbadense, respectively. Phylogenetic analysis revealed that a total of 108 GPAT genes from cotton, Arabidopsis and cacao could be classified into three groups. Furthermore, through comparison, the gene structure analyses indicated that GPAT genes from the same group were highly conserved between Arabidopsis and cotton. Segmental duplication could be the major driver for GPAT gene family expansion in the four cotton species above. Expression patterns of GhGPAT genes were diverse in different tissues. Most GhGPAT genes were induced or suppressed after salt or cold stress in Upland cotton. Eight GhGPAT genes were co-localized with oil and protein quantitative trait locus (QTL) regions. Thirty-two single nucleotide polymorphisms (SNPs) were detected from 12 GhGPAT genes, sixteen of which in nine GhGPAT genes were classified as synonymous, and sixteen SNPs in ten GhGPAT genes non-synonymous. Two SNP markers of the GhGPAT16 and GhGPAT26 genes were significantly correlated with cotton oil content in one of the three field tests. This study shed lights on the molecular evolutionary properties of GPAT genes in cotton, and provided reference for improvement of cotton response to abiotic stress and the genetic improvement of cotton oil content.